2009
DOI: 10.1111/j.1365-3156.2008.02179.x
|View full text |Cite
|
Sign up to set email alerts
|

Free distribution of insecticide treated bed nets to pregnant women in Kinshasa: an effective way to achieve 80% use by women and their newborns

Abstract: Summaryobjective To determine whether long lasting insecticide treated bed nets (LLINs) distributed free of charge to pregnant women at their first antenatal clinic visit in Kinshasa, DRC are used from the time of distribution to delivery and 6 months after delivery.methods Women were enrolled into a cohort study at their first antenatal care (ANC) visit and provided LLINs free of charge. Reported use of these nets was then measured at the time of delivery (n = 328) and in a random sample of women (n = 100) 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 19 publications
4
29
4
Order By: Relevance
“…It has been explained in the Cross River state of Nigeria [29] that educated parents may be better able to appreciate the importance of treated nets in malaria prevention and to understand the information included in the public awareness campaigns which will eventually influence bednet usage by their families. Such associations have also been shown by in Kinshasa-DRC by Pettifor et al [30] and Ndjinga and Minakawa [31] and in Mfou-Cameroon by Tchinda et al [3]. …”
Section: Discussionsupporting
confidence: 66%
“…It has been explained in the Cross River state of Nigeria [29] that educated parents may be better able to appreciate the importance of treated nets in malaria prevention and to understand the information included in the public awareness campaigns which will eventually influence bednet usage by their families. Such associations have also been shown by in Kinshasa-DRC by Pettifor et al [30] and Ndjinga and Minakawa [31] and in Mfou-Cameroon by Tchinda et al [3]. …”
Section: Discussionsupporting
confidence: 66%
“…[5] This shows that the free distribution of the nets is not only cost-effective, [18] but also a fast way of reaching the ITN coverage targets. [19] The study also showed that a large number of the nets were not hanged, improperly deployed and unoccupied. Although this is consistent with the findings in several other communities in Nigeria, [13] it is however contrary to the findings of two other surveys in the State, [20] and elsewhere in the Niger delta.…”
Section: Discussionmentioning
confidence: 93%
“…The included intervention studies evaluated two main channels for delivering ITNs to pregnant women: campaign delivery (non-targeted) [89],[92][94] and routine delivery to pregnant women through ANC services (targeted), with three alternative mechanisms evaluated at ANCs: distribution of free nets with [95]–[97] or without social marketing [98],[99], and distribution of subsidised vouchers [83],[84],[100][102]. One study compared the impact of ANC delivery alone versus ANC delivery plus community-based distribution of subsidised nets in Niger (Table 3).…”
Section: Resultsmentioning
confidence: 99%